Data Collection Information System for Prospective Citizens and Citizens (Trainers) at PSHT Pekanbaru Branch Using the Laravel Framework - Yulisman; Zulkifli, Akhmad; Cindika Gustiani, Dimas (Journal of ICT Applications System, 2023)
The Data Collection System for Prospective Citizens and Residents (Trainers) in the Setia Hati Brotherhood in the Pekanbaru Branch still uses a manual system. Where paper becomes a means in data collection and data information sources. The rapid development of technology in the current era of globalization that can facilitate all respects, including data collection of information that can make data collection more effective and efficient. PSHT Pekanbaru Branch corrects the problem in this data collection to make data collection faster because the system has not been computerized. The data collection in the PSHT Pekanbaru Branch requires a new system so that the system can be improved. As for the system carried out by the writer who discusses structured development systems using the waterfall method, as well as analysis and design tools using the Unified Modeling Language (UML). As for the implementation, some software is published using the framework framework , the code editor uses Atom, the PHP package uses XAMPP version 3.2.4 (PHP 7.3.9, Apache web server 2.4.7 and MySQL database version 5.0.12) and which the last web browser using Google Chrome